Integrating Virtual World Into Project Based Learning Through Teaching And Learning Writing - Amri, Carlina; Tanduklangi, Amri; Alberth, Alberth (Journal of Language Education and Educational Technology (JLEET), 2016)
This research is accomplished to investigate how effective is virtual world instructional mode for teaching and learning writing for EFL learners. The researcher used quantitative data to investigate the effectiveness of using Avakin Life as a substitution class to the regular writing course for the EFL learners. Two research questions then were settled. The first question asked to what extent the virtual classroom instruction helps foreign language English writer increase their proficiency. The second question was intended to measure the degree of participants’ Sense of Community. This participants of this study where the students of English teaching study program of Halu Oleo University who registered in academic year of 2010/2011. The total number of participants involved was 10. In taking sample, the researcher used Convenient Sampling. The instruments of data collection were writing test and a questionnaire. The writing test were administered by assigning pre-test to know students prior knowledge, and post-test to know students writing achievement after giving treatment. The questionnaire was settled into 22 items for Sense of Community. Paired sample t-test was employed to seek the different mean of each group as the comparison before and after receiving the course. The result shows a significant difference between the pre and post of writing proficiency of the treatment class. In addition, the result from the post-instruction questionnaire shows that the participants’ had a high degree on their Sense of Community after being taught writing under the virtual world instructional mode